A Non-randomized Controlled Trial of EMDR on Affective Symptoms in Patients With Glioblastoma Multiforme - Szpringer, Monika; Oledzka, Marzena; Amann, Benedikt L. (Frontiers in Psychology, 2018)
Glioblastoma multiforme (GBM) is a highly aggressive brain cancer and its survival after diagnosis is less than 2 years. Therefore, GBM patients are especially prone to co-occurring psychological conditions such as anxiety and depressive disorders. Furthermore, aggressive medical therapies influence patients’ lives, undermining their sense of meaning and coherence. The main aim of this study was to determine the effectiveness of Eye Movement Desensitization and Reprocessing (EMDR) therapy on anxiety, depression and sense of coherence in patients with GBM. Thirty-seven GBM-diagnosed women were included in this trial and received standard medical care. Of those, 18 patients were treated during 4 months with 10–12 individual EMDR sessions (60-90 minutes each). Nineteen GBM patients were used as a non-randomized control group as they consented to psychological evaluations but not a psychotherapeutic intervention. The groups were homogeneous in terms of gender, age, educational level and treatment. But not in anxiety and depressive levels at baseline. All patients were evaluated at baseline, after treatment (4 months) and at follow-up (further 4 months) by the Hospital Anxiety and Depression Scale (HADS-M) and the Sense of Coherence Scale (SOC-29). Caregivers in both groups were interviewed by the Patient Caregiver Questionnaire after 4 months follow-up. Statistical analyses were conducted using ANOVA statistics, correlation and regression analyses showing a statistically significant decrease in the EMDR group in anxiety, depression and anger, when compared to the experimental group. EMDR therapy had also a positive impact upon the level of coherence in the experimental group, whereas in the control group this declined. Finally, the caregivers observed beneficial outcomes of the EMDR therapy with less anxiety- and anger-related behaviors in patients in the experimental group compared to the control group. This study is the first to show beneficial effects of EMDR therapy in alleviating affective symptoms and improving coherence in a severe medically ill population with GBM.